Civil War, Famine and the Persistence of Human Capital: Evidence from Tajikistan - Louise Grogan (Institute of Labor Economics (IZA), 2021)
The dissolution of the Soviet Union and 1992-96 Tajik civil war resulted in huge human and economic losses. Nevertheless, contemporary data suggest the persistence of investments in human capital in the region most affected by famine and least favoured since the cessation of hostilities, Gorno-Badakhshan Autonomous Oblast. Famine-affected women have greater stature and final educational attainment, later ages at marriage and lower fertility than do those in the neighbouring border province, Khatlon. Educational interactions between adults and children under age six are much more frequent. The continued emphasis on human capital after economic collapse is consistent with a locational imperative for households to earn incomes outside of agriculture, and with a higher relative status of women in non-agrarian societies.
Keywords: H4; J1; 330; food security; anthropometry; schooling; child mortality; early childhood education; civil war; Tajikistan